Nonfunctioning symptomatic paraganglioma: Is there an optimal follow-up for patients with extra-adrenal benign paragangliomas - Mantas, D. (Oxford University Press, 2014)
Paragangliomas are rare neuroendocrine neoplasms originating from the embryological neural crest. In most cases, they exhibit a benign behavior. Here we report a case of a small symptomatic para-aortic paraganglioma, which was completely removed surgically and a review of the available literature regarding the optimal follow-up of a benign paraganglioma, since no guidelines are currently available for this rare entity.